A novel 4-aminoquinoline chemotype with multistage antimalarial activity and lack of cross-resistance with PfCRT and PfMDR1 mutants - Ferreira, Letícia Tiburcio (2024)
Funding Information: This study was supported by Fundação de Amparo à Pesquisa do Estado de São Paulo - FAPESP (2019/02171-3 and 2021/13809-9 to LTF, 2017/18611-7 to FTMC, 2021/06769-0 to DYB, and 2018/24878-9 to JC), Conselho Nacional de Desenvolvimento Científico e Tecnológico – CNPq (441038/2020-4 and 440373/2022-0 to CHA, and 162117/2018-3 to LCSA), and the National Institutes of Health – NIH (R01 AI124678 and R37 AI050234 to DAF, R01 AI147628 to MQ, DAF). CHA was also supported by Fundação de Amparo à Pesquisa do Estado de Goiás (202010267000272). DYB acknowledges funding from Instituto Serrapilheira (G-1709-16618). MP is funded by “la Caixa” (HR21-848) and European Union Horizon Europe programme (101080744). PS was supported by the Swedish Research Council - Vetenskapsrådet (2021-03667) and The Swedish Foundation for International Cooperation in Research and Higher Education - STINT (BR2018-8017). MCSL gratefully acknowledges funding from the Bill and Melinda Gates Foundation (OPP1054480). The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript. Publisher Copyright: Copyright: © 2024 Ferreira et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.